2017
DOI: 10.1021/acs.orglett.7b02517
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Gracilamine and Determination of Its Absolute Configuration

Abstract: (+)-Gracilamine, a biologically attractive and structurally unique pentacyclic Amaryllidaceae alkaloid, was biomimetically synthesized in 11 linear steps in 9.9% overall yield from the known racemic oxocrinine. The synthesis features an asymmetric hydrogenation, a ring-opening/benzylic oxidation/cyclization sequence, and a biomimetic intramolecular cycloaddition. This total synthesis not only allows the assignment of its absolute configuration, but also provides experimental support for the hypothesis that nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…AH of ketones, lactones and -ketoesters using an iridium catalyst based on a P(NH)N spiro ligand by Zhou, Xie and co-workers. [219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] This method provides one of the most impressive recent applications of Ir-bifunctional catalysts in asymmetric hydrogenation, in terms of both catalytic efficiency, enantioselectivity, substrate scope and synthetic potential. It is worth to note that Zhang, Yin and co-workers reported in parallel the synthesis of rather similar oxaspirocyclic chiral ligands and applied them to iridium-catalyzed direct asymmetric hydrogenation of Bringmann's lactones (Scheme 73a).…”
Section: Iridium Catalysts Involving Active Nh Functions and Related ...mentioning
confidence: 97%
See 1 more Smart Citation
“…AH of ketones, lactones and -ketoesters using an iridium catalyst based on a P(NH)N spiro ligand by Zhou, Xie and co-workers. [219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] This method provides one of the most impressive recent applications of Ir-bifunctional catalysts in asymmetric hydrogenation, in terms of both catalytic efficiency, enantioselectivity, substrate scope and synthetic potential. It is worth to note that Zhang, Yin and co-workers reported in parallel the synthesis of rather similar oxaspirocyclic chiral ligands and applied them to iridium-catalyzed direct asymmetric hydrogenation of Bringmann's lactones (Scheme 73a).…”
Section: Iridium Catalysts Involving Active Nh Functions and Related ...mentioning
confidence: 97%
“…[220][221][222][223][224] Moreover, this type of iridium(III) catalyst was involved in several DKR processes and enabled the asymmetric total synthesis of compounds of biological interest like crinine-type alkaloids (Scheme 72c), gracilamine alkaloïds, (-)goniomitine, mulinane diterpenoids, (-)-hamigeran B, (-)-mesembrine and others. [225][226][227][228][229][230][231][232] A recent application to the AH/Dynamic kinetic resolution of racemic α-arylamino-γ-lactones and α-arylamino-δlactones led to the corresponding chiral 2-amino diols with high yields and enantioselectivities (Scheme 72d). [233][234] According to theoretical studies, the hydride and proton transfer step proceeds via a cyclic 6membered transition state.…”
Section: Iridium Catalysts Involving Active Nh Functions and Related ...mentioning
confidence: 99%
“…A biomimetic asymmetric total synthesis of (+) Gracilamine has been reported by Xie & coworkers from rac compound 73. [43] The synthesis features an asymmetric hydrogenation, a ringopening/benzylic oxidation/cyclization sequence, and a biomimetic intramolecular cycloaddition. Compound 73 underwent asymmetrically hydrogenated to give 74 with both trans & cis isomers.…”
Section: Xie's Approachmentioning
confidence: 99%
“…Our group recently reported a Pd-catalyzed decarboxylation process that enabled the [4+1] annulation of VMCCs with amines as reaction partners toward the generation of pyrroles (Scheme 18 ). 27 It is worth mentioning that this methodology could be utilized for the synthesis of a number of tetra- and pentasubstituted pyrroles, which are synthetically challenging. Control experiments indicated that the reaction proceeded via an intermediate Z -configured γ-amino unsaturated ketone.…”
Section: Zwitterionic Enolate Chemistry Based On Transition-metal Cat...mentioning
confidence: 99%